20 Do atriopulmonary (AP) fontan dimensions using CMR influence the development of atrial tachyarrhythmia?. (18th April 2016) - Pickup, L; Quinton, E; Thorne, S; Bowater, S; Clift, P; de Bono, JP; Hudsmith, L
Abstract : Introduction: Atrial tachyarrhythmia is regarded as a late consequence of the Fontan circulation, particularly in those with an AP Fontan and is associated with significant morbidity and mortality. Developing methods to recognise those at the highest risk will allow early intervention, improving patient outcomes. Purpose: To establish relationship between AP Fontan chamber (FC) dimensions, ventricular volumes and function and the development of atrial arrhythmia (AR). Methods: Modified AP Fontan patients with CMR (1.5T, Avanto, Siemens) were reviewed (Figure 1 ). Horizontal long axis (HLA, TrueFISP cine, flip angle 80, TR/TE 50/1.26ms, retrospective ECG gating) and transaxial 3D MRA non-contrast (Modified Siemens Whole Heart coronary artery sequence, respiratory navigator, ECG-triggered, free breathing, slice thickness 2.00mm) of the FC and the left atrium were examined. Results: 55 patients 58% female and 42% male, mean age 33yrs (SD 7.9). 32 patients suffered a documented AR, most commonly atrial flutter (79%). There was a significant difference in age between the two groups with those having an AR tending to be older (36yrs vs 29yrs p < 0.05) the age of procedure was also younger in the AR group (6yrs vs. 10yrs p < 0.05) (Table 1 ). There was no difference in ventricular ejection fraction (p > 0.05). There were no significant differences in atrial parameters between the two groups (p > 0.05), however all measures of the FC were statistically different with larger measures occurring in the AR group (p < 0.05). Receiver operator characteristic curves were constructed for each of the atrium and FC variables. Only end diastolic area and FC longitudinal dimension produced statistically significant results (ROC 0.745 P < 0.05 and 0.719 p < 0.05). Using an upper limit of 27cm 2 for end diastolic FC area odds ratio of AR was 8.57 (p < 0.05) with a sensitivity of 0.596 and a specificity of 0.870. Conclusions: Increasing AP FC size is associated with increased risk of AR.